Beginning database design solutions : understanding and implementing database design concepts for the cloud and beyond - Stephens, Rod (Hoboken, New Jersey : John Wiley & Sons, Inc., 2023)
'In the newly revised second edition of Beginning Database Design Solutions: Understanding and Implementing Database Design Concepts for the Cloud and Beyond, Second Edition, award-winning programming instructor and mathematician Rod Stephens delivers an easy-to-understand guide to designing and implementing databases both in and out of the cloud. Without assuming any prior database design knowledge, the author walks you through the steps you'll need to take to understand, analyze, design, and build databases. In the book, you'll find clear coverage of foundational database concepts along with hands-on examples that help you practice important techniques so you can apply them to your own database designs, as well as: Downloadable source code that illustrates the concepts discussed in the book, Best practices for reliable, platform-agnostic database design, Strategies for digital transformation driven by universally accessible database design. An essential resource for database administrators, data management specialists, and database developers seeking expertise in relational, NoSQL, and hybrid database design both in and out of the cloud, Beginning Database Design Solutions is a hands-on guide ideal for students and practicing professionals alike.'--Publisher's website
Includes index.
Previous edition: 2009.
Keywords: Database design; Databases; Cloud computing